Avaliação dos efeitos da suplementação de alimento à base de milho (cuscuz) sobre a produção de leite materno e ganho de peso das crianças - Linhares, Dyanna Kelly Almeida (2024)
Exclusive breastfeeding is essential for child growth and development, strengthening the mother-child bond and promoting the physical and mental health of both. Recognizing this importance, it is essential to outline strategies that promote breastfeeding, stimulating an increase in milk production and strengthening this practice. This study aimed to evaluate whether dietary supplementation with starch (couscous) in breastfeeding women is capable of providing greater weight gain in the child through breast milk. This is an experimental clinical trial with Crossover. The participants were exclusively breastfeeding women linked to Family Health Centers in the city of Sobral, who were divided into two groups, group A and group B. Mothers allocated to group A started consuming 70 grams of starch in the form of couscous daily. for 20 days, then this same group spent 20 days without consuming starch (Crossover). In group B, in the first 20 days, mothers did not consume starch in the form of couscous, but started consuming it from day 21 to day 40 of the intervention. The children were weighed on days 1, 20 and day 40 after the start of the intervention.The increase in breast milk production was assessed using a Likert scale. Almost two-thirds of mothers reported a large increase in breast milk. The study had a statistically significant result: mothers undergoing starch supplementation (couscous) during the 20 days had an average weight gain in their children of 33.7g per day, breastfeeding mothers who were not using couscous, their children increased by 24.6g per day with p less than 0.0079.